TEACHING VOCABULARY USING DIRECT METHOD AT SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Gunawan Awan Sinaga; Anisa Nur Safitri; Muhamad Efransyah (IKIP Siliwangi, 2018)
Mastering vocabulary is very important, because vocabulary is the main aspect in teaching English. Vocabulary is a set of words for which an individual can assign meanings when he or she listening, speaking, reading or writting. People interact in communication will not be effective if they do not master the vocabulary. Direct method is one of method that can help learner to learn vocabulary by themselves. The objective of this research is to find out whether teaching vocabulary using direct method can improve students’ vocabulary at seventh grade of MTs. Negeri Sukasari. The method of this research was quantitative method. The researchers used one group pretest-posttest design. The population of this research was the seventh grade students of MTs. Negeri Sukasari Cimahi and the sample taken from 31 students. The data of this research were collected by giving pretest and posttest, and the data was assisted by SPSS 23.version. Mean score of pretest was 71.61, while mean score of posttest was 89.68 and Wilcoxon test Asymp. Sig. (2-tailed) significant level was .000. In the other words, the null hypothesis (Ho) was rejected, because the Asymp. Sig. (2-tailed) in Wilcoxon test .000 was lower than 0.05. It means that teaching using direct method can improve the students’ vocabulary.